PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA ANGKRINGAN GIRAS DI SITUBONDO - Arizal, Mohammad Dimas; Hamdun, Edy Kusnadi; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2023)
The angkringan business is also a good plan in terms of attracting consumers and in the current era it is certainly a big opportunity for angkringan entrepreneurs to make it easier to survive and develop an angkringan business. Consumer satisfaction must always be considered for entrepreneurs engaged in the culinary field. Observing consumer satisfaction, consumers feel satisfied in terms of service because it is in accordance with the wishes expected. If the consumer is satisfied, the consumer will definitely come back to make a purchase. Consumer expectations in feeling satisfied or dissatisfied will create high consumer loyalty. The purpose of this study is to determine the quality of service and location of consumer loyalty with consumer satisfaction as an intervening variable at Angkringan Giras in Situbondo. the population in this study is the entire population in this study are all consumers who make purchases at Angkringan Giras Situbondo. After observing and interviewing consumers of Angkringan Giras in Situbondo. Random sampling method (simple probability sampling) without regard to strata in the population in this study. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that service quality has a significant positive effect on consumer satisfaction. Location has a significant negative effect on consumer satisfaction. Service quality has a significant positive effect on consumer loyalty. Location has a significant positive effect on consumer loyalty. Consumer satisfaction has a significant positive effect on consumer loyalty. Service quality has a significant positive effect on consumer loyalty through customer satisfaction. Location has a significant negative effect on customer loyalty through customer satisfaction.